Commercial volume distribution by site index in clonal plantations of Tectona grandis L.f in the Northern Zone of Costa Rica - Barrantes-Madrigal, Katherine (2021)
Forest production requires knowing the volume of marketable diameters. The objective of this study was to generate a volume distribution table according to the minimum commercial diameter for different site index (SI) labels for the Northern Zone of Costa Rica. A sample of 119, 120 and 28 trees established within the forest plantations at the 27 m, 24 and 21 m indices, respectively, the diameters were measured at the stump height, normal diameter at 1.3 m on the stem and the diameters in different sections on the stem with a spacing of 1.5 m until reaching the total height and zero diameter. The volume of each section was obtained with the Smalian formula and the volume of the tree by adding the sections. The following minimum commercial diameters were considered: coarse saw: ≥30 cm in diameter, thin saw: ≥20 <30 cm, pallet: ≥12 <20 cm, firewood: ≥5 <12 cm and waste: <5 cm. The volume for coarse sawmill increased as the diameter of the tree increased. In the 27 m IS, diameters less than 13 cm correspond to 40 % firewood, between 13 cm and 24 cm pallet predominates, henceforth thin sawmills predominate; with more than 28 cm, the coarse and thin sawmills represent more than 75 % of the commercial volume. The five diametric minima evaluated are present in trees that grow at the 27 m and 24 m IS labels; while, in the IS 21 m, no wood for sawmill was recorded. The volume distribution tables by minimum commercial diameter are a useful tool to determine the trend and distribution of commercial volume by type of utility for this species.